2015
DOI: 10.1111/pde.12664
|View full text |Cite
|
Sign up to set email alerts
|

Severe Extravasation Injuries in Neonates: A Report of 34 Cases

Abstract: Extravasation injuries in extremely preterm and low-birthweight infants are more likely to lead to skin necrosis. Peripheral venous catheterization should be performed with caution in these patients to prevent such injuries. Immediate irrigation with normal saline is recommended to reduce toxic sequelae in the infiltrated area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 22 publications
3
55
1
4
Order By: Relevance
“…This was consistent with the literature, which reported that 22% of cases in a neonatal unit involved PIVCs and the rates were 12% in a paediatric intensive care unit and 16% in a paediatric surgical ward . Severe extravasation has been reported in 2.4% to 3.8% of neonates, causing skin necrosis in 0.4% of the cases . The present study did not determine the severity of extravasation, as no grading scale was available in the electronic patient record system.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This was consistent with the literature, which reported that 22% of cases in a neonatal unit involved PIVCs and the rates were 12% in a paediatric intensive care unit and 16% in a paediatric surgical ward . Severe extravasation has been reported in 2.4% to 3.8% of neonates, causing skin necrosis in 0.4% of the cases . The present study did not determine the severity of extravasation, as no grading scale was available in the electronic patient record system.…”
Section: Discussionsupporting
confidence: 92%
“…An extravasation incidence rate of 0.04 per patient day was calculated in another study of paediatric patients between birth and 18 years of age and 93% of these cases involved a PIVC . Severe extravasation has been reported with an incidence of 2.4% in neonates, causing skin necrosis in 0.4% of cases . In another study, 38 per 1000 neonates experienced extravasation with skin necrosis .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Extravasation is the accidental leakage of fluid, such as medication or nutrients, into the surrounding tissue during infusion. Subsequently, this can lead to skin and soft tissue damage and result in severe ischemia, infection, and necrosis …”
Section: Resultsmentioning
confidence: 99%
“…Dünyada kullanılan intravenöz infiltrasyon ölçeklerinde genel olarak infiltrasyon düzeyi gözlemsel bulgulara göre belirlenmektedir (3,16,(20)(21)(22). Düzey belirlemenin ardından yapılacak işlemler kurum politikalarına göre değişmektedir.…”
unclassified